DEVELOPMENT OF PALM SHELL CARBON FOR PYSICS EKSPREIMENT TOOL - Z, Zulpadrianto; Y, Yohandri; Putra, Ananda (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2023)
Research on science experiment practicum media has been carried out. This research is a laboratory experimental research. The aim of the research is to see the absorption of palm shell carbon against electromagnetic waves (RAM). RAM using palm shell carbon will be applied to anechoich chambers in science experiment practicums. Research procedure: carbonized palm shells were then activated using HCl. Activation was carried out with concentrations of 1, 2, 3, 4 and 5 Molar. In addition to the differences in the concentration of the activation substance, variations in the thickness of the print resulting from the activation were also carried out. The thickness of the printed material varies from 4mm, 6mm, 8mm and 10mm. The results of reflection loss measurements using a Vector network analyzer (VNA) at a frequency of 4GHz - 8GHz show differences for each concentration. Maximum reflection loss of palm shells using 1M HCl activation agent (-13.72 dB); 2M (-13.62dB); 3M (-13.35 dB); and 4M (-13.04dB) and 5M (-11.4 dB) concentrations. Variations in print thickness also have a significant effect on the absorber value of a material, the thicker the print results, the absorber value also increases. From the observations that have been made, the maximum absorber value is obtained when the thickness is 10mm at a concentration of 1M for the substance being tested.